Laboratory Sand Tank Modeling of the Brumbys Fault CO2 Controlled Release Field Experiment - Hailun Ni; Andrew Feitz; Eric Tenthorey; Hadi Nourollah; Katherine Romanak; Claire Patterson; Susan Hovorka (Geophysical Research Letters)
Abstract Faults present potential leakage risks for geological CO2 storage. To de‐risk a field test injecting CO2 into a shallow fault, laboratory sand tank fluid flow experiments were conducted prior to field injection. The vertical 2.5D sand tank analog models were constructed with different grain sizes of glass beads to represent the permeability contrast between formation layers. A variety of analog fluids were also used to represent both the injection of gaseous and supercritical CO2. Experimental results have validated the simulation results in terms of fluid migration pathways. In addition, results with different analog fluids show that CO2 migration along faults is likely to have similar overall flow paths both near the surface and at depth, but different plume sizes and saturation. Finally, based on an inspectional scaling analysis, we were able to estimate field‐scale CO2 plume migration time, which has been validated by real field observations for the first time.